Relationships Among Occupation/Activity Patterns, Health and Stress Perceptions, and Life Orientation in Well Adults - Barbara Prudhomme White; Amy Ma; Deborah Whitney (Scholarworks @ WMU, 2014)
Background: This study examined the relationships among activity choices, perceived health, stress, and life orientation (optimism-pessimism) in a general population of 675 healthy adults ranging in age from 18-91 years. The objective was to examine assumptions that occupational scientists and practitioners hold regarding the relationships among health factors and engagement in activities/occupations. Method: The study used four self-report measures, including a customized activity card sort that asked participants about both healthy and unhealthy activity patterns. Responses were then compared with the participants' perceptions of overall health, stress levels, and degrees of optimism and pessimism (life orientation). Results: Major findings confirmed that being engaged in more activities overall is aligned with more optimally perceived health, positive life orientation, and lower stress. However, participation in unhealthy activities negatively affected overall health, stress perception, and life orientation. The study also confirmed that women tend to have higher perceived stress than men and that caring for others is associated with more positive health ratings. Conclusion: The amount and type of activity participation appears to matter for even healthy individuals in terms of overall health, stress perception, and life orientation. This study confirms the importance of participating in a wide repertoire of activities and underscores the need for practitioners to ask clients about engagement in unhealthy activities as well as healthy ones.